Model-based evolutionary analysis: the natural history of phage-shock stress response. (22nd July 2009) - Huvet, Maxime; Toni, Tina; Tan, Hui; Jovanovic, Goran; Engl, Christoph; Buck, Martin; Stumpf, Michael P.H.
Abstract : The evolution of proteins is inseparably linked to their function. Because most biological processes involve a number of different proteins, it may become impossible to study the evolutionary properties of proteins in isolation. In the present article, we show how simple mechanistic models of biological processes can complement conventional comparative analyses of biological traits. We use the specific example of the phage-shock stress response, which has been well characterized in Escherichia coli, to elucidate patterns of gene sharing and sequence conservation across bacterial species.